Building a conceptual framework for determining individual differences of accessibility to tourist attractions - AlKahtani, S.; Xia, Jianhong (Cecilia); Veenendaaland, B.; Caulfield, C.; Hughes, M. (Elsevier, 2015)
This paper introduces a conceptual framework for determining individual differences of accessibility to tourist attractions. The framework includes three components: factors affecting accessibility to tourist attractions; the individual characteristics of tourists, such as age, gender; and other explanatory variables that assist in explaining why accessibility to tourist attractions varies. This research indicates that measures of accessibility should include not only commonly used factors such as socio-demographic variables and distance, but also the facilities available at various attractions, management and operational aspects relating to the attraction (what we term "functions"), and the infrastructure used to move between specific attractions (what we term "connectivity of networks"). A case study of the Ningaloo Coast region was conducted to identify individual difference in evaluation of accessibility to tourist attractions. We show that the evaluation of accessibility varies among tourist groups due to their spatial abilities, individual values and needs, and preparatory set.